Acute health symptoms related to perception and practice of pesticides use among farmers from all regions of Thailand - Sapbamrer, Ratana; Sittitoon, Nalin; Thongtip, Sakesun; Chaipin, Eakasit; Sutalangka, Chatchada; Chaiut, Wilawan; La-up, Aroon; Thirarattanasunthon, Phiman; Thammachai, Ajchamon; Suwannakul, Boonsita; Sangkarit, Noppharath; Kitro, Amornphat; et al. (Frontiers in Public Health, 2024)
Occupational exposure to pesticides may cause acute health effects for farmers and agricultural workers. Therefore, this study aims to investigate the prevalence of poisoning symptoms related pesticide exposure among farmers from all regions of Thailand, as well as factors linked to poisoning symptoms of neurological and neuromuscular systems, the respiratory system, and eye and skin disorders. A cross sectional study was conducted in 4,035 farmers who lived in four regions of Thailand. The samples were chosen using stratified random sampling, with 746 for the Central region, 2,065 for the North-East, 586 for the North, and 638 for the South. The results found that the highest prevalence of poisoning symptoms was found in association with neurological and neuromuscular systems (75%), followed by the respiratory system (60.4%), the eyes (41.2%), and skin (14.8%). The most prevalent symptoms were muscle pain ( 49%) for neurological and neuromuscular symptoms, burning nose ( 37. 6%) for respiratory symptoms, itchy eyes ( 26. 3%) for eye symptoms, and rashes (14.4%) for skin symptoms. The remarkable findings were that types of pesticide use, task on the farm, types of pesticide sprayers, and perception are the crucial factors affecting all poisoning symptoms. The findings are also beneficial to the Thai government and other relevant organizations for launching Acute Health Symptoms Related to Perception and Practice measures, campaigns, or interventions to lower modifiable risk factors, resulting in reducing health risks associated with pesticide exposure.